Carbon nanotubes suspended dusty nanofluid flow over stretching porous rotating disk with non-uniform heat source/sink. Issue 2 (4th March 2022) - Naveen Kumar, R.; Mallikarjuna, Hogarehally Basavarajappa; Tigalappa, Nirmala; Punith Gowda, R. J.; Umrao Sarwe, Deepak
Abstract: The current paper explores the flow of dusty nanoliquid over a rotating and stretchable disk with non-uniform heat sink/source. Further, we have done a comparative study on Single wall carbon nanotubes (SWCNT)-water and multi wall carbon nanotubes (MWCNT)-water based dusty fluid flows. By means of apt similarity variables, the governing equations are converted to set of nonlinear ordinary differential equations and then they are numerically tackled using Runge–Kutta–Fehlberg's fourth fifth order (RKF45) method by adopting shooting technique. The influence of non-dimensional parameters on the heat transfer fields are incorporated and extensively discussed by means of appropriate graphs. Further, the reduced shear stresses at the disk in the tangential direction, in the radial direction and the heat transference rates of the fluid and particles are deliberated graphically. Results reveal that, the escalating values of space and temperature dependent heat source/sink parameters improves the heat transference of both liquids. The SWCNT-water based fluid shows improved shear stress in tangential and radial direction when compared to MWCNT-water based fluid for both the phases. The SWCNT-water based fluid shows enhanced heat transfer rate than MWCNT-water based fluid for both fluid and dust phases.